Editorial for Special Issue “Present and Past Submarine Volcanic Activity (1)” - Riccardo De Ritis; Salvatore Passaro; Alessandra Pensa (Geosciences, 2022)
Over 1 million volcanoes on the Earth surface occur in marine and submarine environments in different geodynamic contexts [...]